THE DOUBLE BIND OF FEMININITY: THE LIKEABILITY PENALTY AND THE COMPETENCE–ATTRACTIVENESS PARADOX AMONG WORKING WOMEN IN MEDAN - Sinaga, Triana Melinda; Sofyan, Silvia; Hidayat, Ferry (Penerbit Lafadz Jaya, 2025)
Women in the formal workforce often face a double bind dilemma, where the need to demonstrate competence conflicts with expectations of femininity. This study analyzes the influence of the likeability penalty and the competence–attractiveness paradox on promotion opportunities and work engagement among female employees in Medan. A quantitative explanatory design was applied, with data from 100 respondents selected through purposive sampling. A five-point Likert scale questionnaire was used, and data were analyzed using Partial Least Squares Structural Equation Modeling (SEM-PLS). Results indicate that the likeability penalty negatively affects promotion opportunities (β = -0.296; p = 0.008), while the competence–attractiveness paradox has a dual effect: positively influencing perceived competence (β = 0.318; p = 0.004) but negatively affecting promotion opportunities (β = -0.211; p = 0.029). Promotion opportunities significantly improve work engagement (β = 0.427; p = 0.000). These findings underscore persistent gender bias, aligning with Role Congruity Theory, and highlight the need for competence-based promotion policies.